Automatic image–text alignment for large-scale web image indexing and retrieval. Issue 1 (January 2015) - Zhou, Ning; Fan, Jianping
Abstract In this paper, an automatic image–text alignment algorithm is developed to achieve more effective indexing and retrieval of large-scale web images by aligning web images with their most relevant auxiliary text terms or phrases. First, a large number of cross-media web pages (which contain web images and their auxiliary texts) are crawled and segmented into a set of image–text pairs (informative web images and their associated text terms or phrases). Second, near-duplicate image clustering is used to group large-scale web images into a set of clusters of near-duplicate images according to their visual similarities. The near-duplicate web images in the same cluster share similar semantics and are simultaneously associated with a same or similar set of auxiliary text terms or phrases which co-occur frequently in the relevant text blocks, thus performing near-duplicate image clustering can significantly reduce the uncertainty on the relatedness between the semantics of web images and their auxiliary text terms or phrases. Finally, random walk is performed over a phrase correlation network to achieve more precise image–text alignment by refining the relevance scores between the web images and their auxiliary text terms or phrases. Our experiments on algorithm evaluation have achieved very positive results on large-scale cross-media web pages.